The Future Wheel Model of the Effects of the Emerging Infectious Diseases Pandemics on the Elderly in Iran - Zohreh Nejatzadehgan Eidgahi; Reza Dehnavieh; Vahidreza Borhaninejad; Alireza Alikhani; Vajihe Rouhi (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives During the outbreak of the infectious diseases, the elderly are at a higher risk. The future wheel model can help understand the different dimensions and effects of these diseases. The present study aims to determine the different effects of the emerging infectious disease pandemics on elderly people based on the experiences from the COVID-19 pandemic in Iran using the future wheel model. Methods & Materials In this qualitative expert-oriented study conducted in 2022, the second version of the future wheel was used to identify the effects in three steps. First, the effects were extracted by brainstorming method with a panel of experts (the Aging Committee of the Research Institute for Future Studies in Health, Kerman, Iran). Then, the effects were analyzed with the STEEP method and in interaction with other two panel of experts. In the next step, the effects were examined, and after reaching a consensus, the future wheel of the effects and their time horizon was provided. Results In this study, 81 effects of the emerging infectious disease pandemics on the elderly were identified in 6 dimensions of socio-psychological (n=25), technological (n=3), economic (n=7), environmental (n=1), political (n=3), and health (n=38). Of these, 10 opportunities and 9 threats and their time horizons were extracted.  Conclusion The outbreak of the emerging infectious diseases such as COVID-19 can leave multi-dimensional effects on the elderly in the world including Iran. We can take advantage of the experiences of facing the COVID-19 pandemic and consider the requirements and solutions for dealing with similar pandemics in the future.